PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum) TERHADAP PEMBERIAN BOKASHI KALAKAI (Stenochlaena palustris) PADA TANAH GAMBUT PEDALAMAN - Jakunda A; Syahrudin Syahrudin; Suparno Suparno; Asie K., V., (Fakultas Pertanian Universitas Palangka Raya, 2020)
The purpose of this experiment was to study the growth and yield of onion (Allium ascalonicum) on the giving of bokashi kalakai on peat land. This study used Randomized Compete Design (RCD) of single factor that was bokashi kalakai consisting of 6 levels of treatment namely P0 (0 ton ha-1), P1 (3 ton ha-1), P2 (6 ton ha-1), P3 (9 ton ha-1), P4 (12 ton ha-1) and P5 (15 ton ha-1). The results showed that the administration of bokashi kalakia at dose 15 ton ha-1 was the best treatment on all parameter observed including the palant height, the leves number, the leaves area, the number of tillers, the number of bulbs, fresh weight of plants, dry and heavy dry bulbs. However, at a dose treatment of 15 ton ha-1 did not indicate any differences when compared to those at a dose of 12 ton ha-1